ECONOMIC, SOCIAL AND POLITICAL CHANGES AND CHALLENGES OF THE MIGRATION TRENDS - Pejkovski, Jovan (Ревија за социјална политика/Journal of Social Policy, 2016)
The modern migratory movements are expressed through new forms and ways of migrations. The trends which are observed differ from current knowledge of these processes. Europe as a continent and all countries individually are faced with complex situations economically, socially and politically. Waves of migrants, refugees from wars, together with hidden potential terrorists, smugglers of people in huge numbers are flocking from the South to the North. The routes through which these people are moving are touching more or less all European countries. What are the consequences of these changes and how to perceive their scope and coverage? How it will affect the countries through which migrants are passing and especially those in which they intend to stay permanently? What are the costs which have to submit the recipient countries of migrants, and what benefits can be obtained from the persons who are motivated to work? What are the impacts on the labor market and competition between indigenous and migrant workers? All these issues are subject of interest in this paper. It’s about complex issues that are preoccupying people daily and are looking for answers and actions. Activities should be focus on discovering what changes are needed in the policies on migration, education, social protection, health, housing, security, an efficient border management, and other aspects that need to be presented in this paper.